Influence of different MDP concentrations on the bond strength of a resin cement to zirconia - Llerena Icochea, Alfredo Esteban (2016)
The composition of dental adhesives may influence their performance when used for adhesion to dental structures or ceramics. The purpose of the present study was to evaluate influence of different MDP concentrations on the shear bond strength of a resin cement to zirconia. Six experimental adhesives were prepared with the following composition: 0.50 % CQ by wt, 1.0 % DABE by wt, 0.20% BHT by wt, 0.45% DPHIF by wt, 10% HEMA by wt, 15% TEGDMA by wt, 25% BIS-EMA by wt, 10% ethanol by wt, 25% UDMA by wt, and 12.85% BIS-GMA by wt . The MDP monomer was added at 0% by wt, 3% by wt, 6% by wt, 9% by wt, 12% by wt, or 15% by wt. As a control, four commercially available adhesives were evaluated: Single Bond Universal, Single Bond 2, Ambar and Signum Zirconia Bond. The shear bond strength to zirconia was evaluated in a universal testing machine. Failure modes were analyzed with a stereoscopic loupe. Statistical analyses were performed with one-way Anova and Tukeys HSD test ( = 0.05). There were significant differences between groups (p < 0.00001). The highest shear bond strength values were obtained with Signum Zirconia Bond and Single Bond Universal. Singlebond 2 showed the lowest values. There were no differences between experimental adhesives. All groups showed adhesive failures. MDP-containing adhesives are important for bonding resin cements to zirconia, however, the concentration of MDP is not the only factor to be considered.